Spiritual Transformation of Han: Four Levels of Transference in Self Psychology - Oh, Whachul (Journal of pastoral care & counseling, 2021)
The purpose of this article is to research han (an oppressed feeling in Korea) through spiritual approaches including self psychology. Han is an oppressive feeling in Korean society. This han, caused by splitting, can be a place for the beginning of healing. One can invest one’s instinctual energy in the right place in the feeble self, according to one’s deepest needs there, in that spot of fragility. Many Koreans have been suffering from a deceptive self-image and do not feel deserving of love or care because of the vicious han-ridden circle. If Koreans can attain healthy self-object experiences, they will no longer feel fragility in themselves